MANAJEMEN KEGIATAN KEPUTRIAN DI PONDOK PESANTREN HASANKA PALANGKA RAYA - Nusaimah Rhahimah; Musyarapah Musyarapah; Syahmidi Syahmidi (Jurnal Manajemen Pendidikan, 2026)
Islamic boarding schools are Islamic educational institutions that play an important role in shaping a generation with noble character and a strong understanding of religion. In addition to emphasizing religious learning, Islamic boarding schools also function as centers for character building through various structured religious activities. One such activity is the keputrian program, which aims to increase Islamic understanding and shape the religious character of female students. This study aims to analyze the management of women's activities at the Hasanka Islamic Boarding School in Palangka Raya, focusing on the functions of planning and implementation. This study uses a descriptive qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study show that the planning of women's activities is carried out through deliberations by the teachers' council, which includes determining objectives, preparing materials, learning methods, and scheduling activities. The activities are carried out routinely every Saturday morning through lectures, question and answer sessions, and worship practices accompanied by evaluations to measure the female students' understanding on an ongoing basis.